Intensive cognitive therapy for PTSD: a feasibility study. - Ehlers, A; Clark, D; Hackmann, A; Grey, N; Liness, S; Wild, J; Manley, J; Waddington, L; McManus, F (2010)
BACKGROUND: Cognitive Behaviour Therapy (CBT) of anxiety disorders is usually delivered in weekly or biweekly sessions. There is evidence that intensive CBT can be effective in phobias and obsessive compulsive disorder. Studies of intensive CBT for posttraumatic stress disorder (PTSD) are lacking. METHOD: A feasibility study tested the acceptability and efficacy of an intensive version of Cognitive Therapy for PTSD (CT-PTSD) in 14 patients drawn from consecutive referrals. Patients received up to 18 hours of therapy over a period of 5 to 7 working days, followed by 1 session a week later and up to 3 follow-up sessions. RESULTS: Intensive CT-PTSD was well tolerated and 85.7 % of patients no longer had PTSD at the end of treatment. Patients treated with intensive CT-PTSD achieved similar overall outcomes as a comparable group of patients treated with weekly CT-PTSD in an earlier study, but the intensive treatment improved PTSD symptoms over a shorter period of time and led to greater reductions in depression. CONCLUSIONS: The results suggest that intensive CT-PTSD is a feasible and promising alternative to weekly treatment that warrants further evaluation in randomized trials.